Pemahaman Siswa dan Guru terhadap Konsep Pendidikan Hijau sebagai Sarana Pembentukan Karakter Islami di MTs Asih Putera Cimahi - Kunkun Syaeful Millah; Sri Wulan; Uus Ruswandi; Tatang Muh Nasir (At Turots: Jurnal Pendidikan Islam, 2024)
Green Education represents an instructional paradigm that integrates environmental sustainability principles with Islamic character values in the learning process. This study aims to examine the understanding and implementation of Green Education among students and educators at MTs Asih Putera Cimahi as a mechanism for cultivating Islamic character. A mixed-methods approach was employed, utilizing both quantitative and qualitative data collected through surveys and interviews with purposively selected participants. The findings reveal that 78% of students demonstrate a strong grasp of Green Education concepts, while 22% require further clarification. Among educators, 85% have successfully incorporated these principles into their teaching practices, though 15% still face challenges. Key supporting factors include the availability of facilities (72%), integration of environmentally oriented curricula (68%), and institutional support (81%). However, notable obstacles include the lack of specific instructional materials (60%) and insufficient teacher training (55%). The study concludes that Green Education is moderately well-understood and applied, though improvements in training, materials, and student engagement are recommended.